Circadian Rhythm of Body Color Change in the Juvenile Chinese Giant Salamander (Andrias davidianus) Under Different Photoperiods - Yifang Zhang; Ziteng Wang; Qinghua Luo; Honghui Li; Pei Wang; Jiuxiang Wang; Dafeng Li; Wentao Wang; Kangle Yuan; Yan Zhou; Shouliang Luo; He Tian (Animals)
The circadian rhythm of an animal’s body color change is crucial for its survival and adaptation to the environment, with photoperiod serving as a primary “zeitgeber” that significantly affects the circadian rhythm of color change. To explore the circadian body color change in juvenile Chinese giant salamanders (Andrias davidianus), four distinct photoperiod regimens were established, including the DD group (constant darkness), the LD12:12 group (12 h photophase, 12 h scotophase), the LD16:8 group (16 h photophase, 8 h scotophase), and the LD8:16 group (8 h photophase, 16 h scotophase). Reflectance spectra of dorsal skin were measured every 4 h over a 24 h cycle, with data collected every other day for three consecutive days, totaling 72 h. Reflectance spectra were converted into colorimetric variables to analyze circadian patterns. The results demonstrated that juvenile A. davidianus exhibited highly significant circadian rhythmicity under different photoperiods, with their body color becoming darker during the photophase (mean brightness: 14.650 ± 0.629 to 16.385 ± 1.301) and lighter during the scotophase (mean brightness: 16.473 ± 0.875 to 34.422 ± 2.692). Photoperiod alterations significantly affected the rhythm parameters (mesor, amplitude, and acrophase) of mean brightness variation. Compared with the LD12:12 group, the LD16:8 group (extended photophase) reduced rhythm mesor by 1.415, decreased amplitude by 0.988, and induced a 1.510 h acrophase delay. Conversely, the LD8:16 group (extended scotophase) increased rhythm mesor by 2.141 and amplitude by 2.919. These findings indicate that the circadian rhythm of body color change in juvenile A. davidianus is coordinately regulated by endogenous circadian rhythms and exogenous photoperiodic signals. The findings of this study provide a theoretical foundation for the conservation and management of A. davidianus.